2015
DOI: 10.1002/etc.2863
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation kinetics of the conventional energetics TNT and RDX relative to insensitive munitions constituents DNAN and NTO in Rana pipiens tadpoles

Abstract: The manufacturing of explosives and their loading, assembling, and packing into munitions for use in testing on training sites or battlefields has resulted in contamination of terrestrial and aquatic sites that may pose risk to populations of sensitive species. The bioaccumulative potential of the conventional explosives 2,4,6-trinitrotoluene (TNT) and hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and of the insensitive munitions (i.e., less shock sensitive) compound 2,4-dinitroanisole (DNAN) were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(78 reference statements)
1
12
0
Order By: Relevance
“…The companion study to the present study, described in Lotufo et al [22], reported a bioconcentration factor of 0.9 mg/L for TNT in R. pipiens tadpoles. Furthermore, Lotufo et al [22] demonstrated that the body residue of TNT approaches steady state in as little as 1 h and that TNT also depurates rapidly, achieving non-detectible tissue concentrations in less than 6 h upon transfer to clean water. In total, these results indicate that TNT body residues in R. pipiens tadpoles are expected to closely track the concentration of TNT in water.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The companion study to the present study, described in Lotufo et al [22], reported a bioconcentration factor of 0.9 mg/L for TNT in R. pipiens tadpoles. Furthermore, Lotufo et al [22] demonstrated that the body residue of TNT approaches steady state in as little as 1 h and that TNT also depurates rapidly, achieving non-detectible tissue concentrations in less than 6 h upon transfer to clean water. In total, these results indicate that TNT body residues in R. pipiens tadpoles are expected to closely track the concentration of TNT in water.…”
supporting
confidence: 60%
“…Similar to TNT, both DNAN and NTO were not observed to bioconcentrate in R. pipiens tadpoles, with each having a bioconcentration factor < 1, and had even more rapid uptake and elimination kinetics than TNT . These results indicate that DNAN and NTO body residues in R. pipiens tadpoles closely track environmental concentrations (in water); however, the tadpoles do not appear to be as adversely affected by sustained tissue residues of DNAN and NTO compared with TNT.…”
Section: Discussionmentioning
confidence: 76%
“…Among aquatic species, the toxicity of DNAN has been reported for the microalga Pseudokirchneriella subcapitata , the bioluminescent bacterium Vibrio fischeri , the cladocerans Ceriodaphnia dubia and Daphnia pulex , the fathead minnow Pimephales promelas , and tadpoles of Rana pipiens . In addition, exposures of R. pipiens tadpoles to water dosed with DNAN resulted in very low bioconcentration factors (BCFs, <2 L/kg) and rapid depuration of body burdens after transfer to clean water (elimination half‐life <1.2 h) . Limited information on the toxicity and bioaccumulation of DNAN in soil invertebrates is available.…”
Section: Introductionmentioning
confidence: 99%
“…A log K ow value greater than 5 is a predictive indicator for bioaccumulation. Unlike famously bioconcentrating organic pollutants such as DDT (dichlorodiphenyltrichloroethane) and polychlorinated biphenyls (PCBs), which have log K ow values of 4.89 to 6.91; and upwards of 6.47, respectively, values for TNT, DNAN, RDX, and NTO are low, and these compounds, fortunately, have a correspondingly low tendency to bioconcentrate (Lotufo et al 2015).…”
Section: Nitraminesmentioning
confidence: 99%